2002
DOI: 10.1113/jphysiol.2002.018135
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial and skeletal muscle glucose uptake during exercise in humans

Abstract: The purpose of this study was to investigate the effects of exercise on myocardial glucose uptake and whether the pattern of glucose uptake is the same as in skeletal muscle. Glucose uptake was measured using positron emission tomography (PET) and 2- ]FDG was injected 10 min after the start of exercise and exercise continued for a further 25 min. Myocardial and skeletal muscle PET scanning was commenced directly after the completion of the exercise bout. As compared to the resting state, exercise doubled myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
111
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 33 publications
16
111
0
Order By: Relevance
“…[ 18 F]Fluorodeoxyglucose (FDG) is retained within the cell and can be quantified using PET [33]. FDG (5 MBq/kg) was injected 10 min post exercise initiation and exercise proceeded for an additional 20 min [34,35]. Blood samples were taken for metabolite analysis immediately prior to FDG injection, and at 20 and 60 min post-injection.…”
Section: Exercise Intervention and [ 18 F]fluorodeoxyglucose Petmentioning
confidence: 99%
“…[ 18 F]Fluorodeoxyglucose (FDG) is retained within the cell and can be quantified using PET [33]. FDG (5 MBq/kg) was injected 10 min post exercise initiation and exercise proceeded for an additional 20 min [34,35]. Blood samples were taken for metabolite analysis immediately prior to FDG injection, and at 20 and 60 min post-injection.…”
Section: Exercise Intervention and [ 18 F]fluorodeoxyglucose Petmentioning
confidence: 99%
“…Clearly, this is not the case in vivo where resting lactate levels are Ϸ1 mmol/L and can easily reach Ն5 mmol/L in response to exercise, trauma, or stress. 22,23 As shown in Table 2, both lactate and pyruvate contribute significantly to oxidative ATP production. It is noteworthy that even though lactate is present at a 5-fold-lower concentration than glucose in the control group, its contribution to ATP production is Ͼ3-fold higher.…”
Section: Wang Et Al Cardiac Metabolism and Function After Ischemia 2069mentioning
confidence: 99%
“…This is despite the fact that the myocardium is capable of utilizing a wide variety of fuels for oxidative energy production. At rest, circulating lactate concentrations are ϳ1 mM (Table 1) and during moderate exercise can easily reach up to 3-5 mM (37). More than 20 years ago, Drake et al (20) showed that the uptake of lactate by the heart in vivo is directly proportional to its serum concentration.…”
mentioning
confidence: 99%